2021
DOI: 10.1111/jfpp.15695
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on phenolic compounds and bioactive properties of five mushroom species via chemometric approach

Abstract: Mushrooms are considered as valuable foods in many cultures due to their unique aroma, taste, nutritional properties, and biological activities (Ferreira et al., 2010;Heleno, Barros, et al., 2015). Although there is a long past of the utilization of mushrooms by human beings for food and medical purposes, scientific interest in examining their secondary metabolites and chemical composition has started to increase in recent years (Paterson, 2006). Mushrooms are possible sources of different antimicrobial, antit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Interesting, especially from the point of view of food producers, is the presence of fumaric acid in the fruiting bodies of parasol mushroom [ 113 ]. This substance is used as a preservative, acidity regulator, and antioxidant in food production processes (E297).…”
Section: Nutritional Value Of the Parasol Mushroom Fruiting Bodiesmentioning
confidence: 99%
“…Interesting, especially from the point of view of food producers, is the presence of fumaric acid in the fruiting bodies of parasol mushroom [ 113 ]. This substance is used as a preservative, acidity regulator, and antioxidant in food production processes (E297).…”
Section: Nutritional Value Of the Parasol Mushroom Fruiting Bodiesmentioning
confidence: 99%
“…23 Also, phenolic and triterpene compounds and antioxidant, antiproliferative, and anticholinesterase activities of different extracts of this mushroom were investigated in earlier studies. 24,25 In recent years, the remarkable bioactive properties of mushrooms have been attributed to their polysaccharide contents, and interest in the study of polysaccharides has increased. When no studies have been reported on H. pudorinus and C. truncatus polysaccharides, there are limited number of studies on C. tubaeformis and M. procera polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…procera . Also, phenolic and triterpene compounds and antioxidant, antiproliferative, and anticholinesterase activities of different extracts of this mushroom were investigated in earlier studies. , …”
Section: Introductionmentioning
confidence: 99%
“…15 It is also known as a parasol mushroom on account of the large and conspicuous fruiting body like a parasol. 16,17 Abundant nutritional contents and bioactive substances have been identified in M. procera, such as polysaccharides, phenolic compounds, triterpenes, sterols, fatty acids, free amino acids and organic acids. 18,19 Therefore, in addition to being considered a popular food source, especially in Europe, the diverse bioactive properties of M. procera have also aroused people's concerns.…”
Section: Introductionmentioning
confidence: 99%